Bordering two unions : Northern Ireland and Brexit - Mars, Sylvia de; Murray, Colin (Colin R. G.); O'Donoghue, Aoife, 1981-; Warwick, Ben (Policy Press, 2018)
This thorough analysis draws upon EU, UK, Irish and international law and sets the scene for a post-Brexit Northern Ireland by showing what the future might hold.
Keywords: European Union -- Great Britain.; European Union; Northern Ireland -- Politics and government.; Irlande du Nord -- Politique et gouvernement.; Politics and government; Great Britain; Northern Ireland